Effect of different luting systems on the microtensile bond strength of CAD/CAM resin blocks: pilot study - Delgado, Carla Sofia Luzio Ribeiro (2018)
Trabalho Final do Mestrado Integrado em Medicina Dentária apresentado à Faculdade de Medicina